ANALISIS TREND EFEKTIVITAS, EFISIENSI, DAN KEMANDIRIAN KEUANGAN DAERAH KABUPATEN JEPARA - Lisa Robiatu Sakdiyah (Universitas Prof.Hazairin,SH Bengkulu, 2021)
The purpose of this study was to determine the development of the regional financial capacity of the Jepara Regency Government in 2013 - 2019 based on the effectiveness, efficiency, and financial independence of the region and its trends in 2020 - 2025. This study used secondary data from the 2013 Jepara Regency Budget Realization Report (LRA) until 2019. These types of research are quantitative descriptive research. The analytical tools in this study are the ratio of effectiveness, efficiency ratio, and the ratio of regional financial independence. As well as the trend of effectiveness, efficiency, and regional financial independence. The results of the analysis show that the regional financial effectiveness ratio is included in the criteria, the regional financial efficiency ratio with an average of 97.11% in a less efficient position, and the regional financial independence ratio with an average of 22.47% in an instructive position. Then the effective and efficient trend shows the direction of downward development and tends to increase. It is hoped that the local government of Jepara Regency will be able to look for characteristics and explore the potential of the region it has in an effort to maximize PAD and regional financial independence.